The best is yet to come eaudiobook A novel. - Macomber, Debbie (Random House Audio, 2022)
NEW YORK TIMES BESTSELLER • When a woman alone in the world bravely chooses to open her heart, two lost souls have a new chance at belonging, in this intimate novel from Debbie Macomber. A new beginning in charming Oceanside, Washington, is exactly what Hope Godwin needs after the death of her twin brother. There are plenty of distractions, like her cozy cottage with the slightly nosy landlords next door, and a brewing drama among her students at the local high school. Even having settled quickly into the community, Hope still feels something is still missing. That is, until her landlords convince her to volunteer at their animal shelter. There she meets Shadow, a rescue dog that everyone has given up on. But true to her name, Hope believes he’s worth saving. Like Shadow, shelter volunteer Cade Lincoln Jr. is suffering with injuries most can’t see. A wounded ex-marine, Cade identifies with Shadow, assuming they are both beyond help. Hope senses that what they each need is someone to believe in them, and she has a lot of love to give. As she gains Shadow’s trust, Hope notices Cade begins to open up as well. Finding the courage to be vulnerable again, Cade and Hope take steps toward a relationship, and Hope finally begins to feel at peace in her new home. But Hope’s happiness is put to the test when Cade’s past conflicts resurface, and Hope becomes embroiled in the escalating situation at the high school. Love and compassion are supposed to heal all wounds, but are they enough to help Hope and Cade overcome the pain of their past and the obstacles in the way of a better future?